Experiences of Help From the Perspective of Finnish People Who Self-Harmed During Adolescence. (3rd October 2021) - Miettinen, Tiina Maria; Kaunonen, Marja; Kylmä, Jari; Rissanen, Marja-Liisa; Aho, Anna Liisa
Abstract: Adolescent self-harm is a widespread phenomenon, and a significant problem worldwide. This study describes the experiences of help from the perspective of Finnish people who have suffered self-harm during adolescence. Data were collected from 27 participants as essays and interviews. Participants included both females and males with different backgrounds and treatment experiences. The data were analysed using inductive content analysis. Participants described having received help from other people in informal and formal ways, and they had both positive and negative experiences of help. The results show that several barriers exist for self-harming adolescents to access help, thus improvement in this area are necessary.